2014
DOI: 10.1016/j.pain.2014.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Mirror-image pain is mediated by nerve growth factor produced from tumor necrosis factor alpha-activated satellite glia after peripheral nerve injury

Abstract: Mirror-image pain is characterized by mechanical hypersensitivity on the uninjured mirror-image side. Recent reports favor central mechanisms, but whether peripheral mechanisms are involved remains unclear. We used unilateral spinal nerve ligation (SNL) to induce mirror-image pain in rats. On the mirror-image (contralateral) side, we found that satellite glia in the dorsal root ganglion (DRG) were activated, whereas macrophages/Schwann cells in the DRG and astrocytes/oligodendrocytes/microglia in the dorsal sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 61 publications
2
51
1
Order By: Relevance
“…The observed bilateral behavioral changes that correspond to bilateral cytokine alterations following peripheral neuropathy supports observations from prior reports [29,54-56,90], with other reports demonstrating corresponding changes in glial activation [55,56,91-93]. While neuropathic pain resulting from inflammation and/or trauma to peripheral nerves is most widely characterized as arising from the body region in which the trauma/inflammation occurred, pain may also be perceived as arising from the healthy contralateral (‘mirror-image’) body region [91].…”
Section: Discussionsupporting
confidence: 90%
“…The observed bilateral behavioral changes that correspond to bilateral cytokine alterations following peripheral neuropathy supports observations from prior reports [29,54-56,90], with other reports demonstrating corresponding changes in glial activation [55,56,91-93]. While neuropathic pain resulting from inflammation and/or trauma to peripheral nerves is most widely characterized as arising from the body region in which the trauma/inflammation occurred, pain may also be perceived as arising from the healthy contralateral (‘mirror-image’) body region [91].…”
Section: Discussionsupporting
confidence: 90%
“…In fact, unilateral nerve injury or inflammation also activates satellite glia and macrophages in contralateral DRG of animals with mirror pain (Hatashita et al, 2008;Xie et al, 2006;Zhou et al, 1996). TNF-a that diffuses from the injured side via cerebrospinal fluid (CSF) activates satellite glia in contralateral DRG, which then produces extra nerve growth factor to enhance nociceptor excitability after spinal nerve ligation (Cheng et al, 2014). In this report, the contralateral increases of calpain-2 (Fig.…”
Section: Motor Fiber Injury Induces the Early Activation Of Calpain-2mentioning
confidence: 64%
“…3B) and IL-6 ( Fig. 4B) soon after L5-VRT might result from the ipsilateral diffusion by CSF (Cheng et al, 2014) or blood way (Zanjani et al, 2006).…”
Section: Motor Fiber Injury Induces the Early Activation Of Calpain-2mentioning
confidence: 96%
“…A contralateral response might be induced by a glial cell inflammatory response with subsequent release of cytokines leading to activation of central neural nociceptive pathways 24. However, one study showed a peripheral pathway where unilateral nerve injury led to production of tumor necrosis factor alpha (TNF-α) in the dorsal root ganglion (DRG) on the affected side 25. It was hypothesized that TNF-α may diffuse via cerebrospinal fluid toward the contralateral DRG.…”
Section: Discussionmentioning
confidence: 99%
“…It was hypothesized that TNF-α may diffuse via cerebrospinal fluid toward the contralateral DRG. TNF-α subsequently activates satellite glia to produce nerve growth factor leading to long-lasting mechanical hypersensitivity leading to mirroring of pain 25. While there is thus evidence supporting both mechanisms, further studying of this rare phenomenon is warranted to uncover transmedian signaling mechanisms as well to improve our understanding of how brain activity “connects” both sides of the body.…”
Section: Discussionmentioning
confidence: 99%